The study of UV protection materials - S. Wirunchit; C. Apivitcholchat; T. Chodjarusawad; W. Koetniyom (My University, 2018)
Most people are aware of how harmful UV radiation is to the skin. The sun's ultraviolet rays, UVA and UVB, are known to cause skin damage, from freckling and moles to fatal skin cancer. That's why it is important to apply sunscreen products to your skin, to help you stay sun safe and absorber harmful ultraviolet rays. This research is studied to focus on how to make UV materials to protect UV radiation. The UV absorber additive materials are 4 types; nanoZnO solid powder at size 25-50 nm (ZnO-1), nanoZnO 40%wt in ethanol solution (ZnO-2), nano TiO2 solid powder at size 17-50 nm (TiO2-1) and nano TiO2 solid powder 325 mesh (TiO2-2) respectively, that was mixed in pure baby lotion cream. Three concentration of UV absorber additive materials are 5, 10 and 15 % by weight were compared with pure baby lotion cream. All compositions were tested UV absorbance with UV spectroscopy together with studied micro structure of UV absorber additive materials by Field emission scanning electron microscope (FE-SEM). The techniques to confirm UV absorber materials are X-ray diffraction (XRD), Raman and Fourier transform infrared (FT-IR) spectroscopy. From these results were shown the uncertainty of each concentration of UV absorber materials because of the most of the films were not uniform dispersion and depended on the coating technique. This study evaluated the performance of ultraviolet transmission on of different materials by using a single energy light emitting diode as light source. Titanium dioxide (TiO2) and zinc oxide (ZnO) are two of most popular inorganic ultraviolet protective materials in UV protection skin care products was studied.
Keywords: Ultraviolet; Absorbance; Titanium Dioxide; Ultraviolet visible spectroscopy; Skin Protection and Aging